Insights Into the Interfacial Degradation of High-Voltage All-Solid-State Lithium Batteries - Li, Jiawen; Ji, Yuchen; Song, Haoran; Chen, Shiming; Ding, Shouxiang; Zhang, Bingkai; Yang, Luyi; Song, Yongli; Pan, Feng (Nano-Micro Letters, 2022)
Poly(ethylene oxide) (PEO)-based solid polymer electrolyte (SPE) is considered as a promising solid-state electrolyte for all-solid-state lithium batteries (ASSLBs). Nevertheless, the poor interfacial stability with high-voltage cathode materials (e.g., LiCoO2) restricts its application in high energy density solid-state batteries. Herein, high-voltage stable Li3AlF6 protective layer is coated on the surface of LiCoO2 particle to improve the performance and investigate the failure mechanism of PEO-based ASSLBs. The phase transition unveils that chemical redox reaction occurs between the highly reactive LiCoO2 surface and PEO-based SPE, resulting in structure collapse of LiCoO2, hence the poor cycle performance of PEO-based ASSLBs with LiCoO2 at charging voltage of 4.2 V vs Li/Li+. By sharp contrast, no obvious structure change can be found at the surface of Li3AlF6-coated LiCoO2, and the original layered phase was well retained. When the charging voltage reaches up to 4.5 V vs Li/Li+, the intensive electrochemical decomposition of PEO-based SPE occurs, leading to the constant increase of cell impedance and directly causing the poor performance. This work not only provides important supplement to the failure mechanism of PEO-based batteries with LiCoO2, but also presents a universal strategy to retain structure stability of cathode–electrolyte interface in high-voltage ASSLBs. Highlights: 1 The cycle performance of poly(ethylene oxide) (PEO)-based all-solid-state lithium batteries with LiCoO2 cathode was greatly improved via coating LiCoO2 with high-voltage stable Li3AlF6. 2 At the upper cutoff voltage of 4.2 V, the poor electrochemical performance is mainly originated from the structure collapse of LiCoO2 at the surface instead of the decomposition of PEO. 3 When the voltage reaches 4.5 V or even higher potentials, the intensive electrochemical decomposition of PEO-based solid polymer electrolyte accelerated interfacial degradation.